Antibacterial and Antifungal Activity of Galam (Melaleuca cajuputi subsp. Cumingiana (Turcz.) Barlow) Extract against E. coli bacteria and C. albicans fungi - Isnaini Isnaini; Agung Biworo; Husnul Khatimah; Khusnan Mustofa Gufron; Shafa Rahmani Puteri (Journal of Agromedicine and Medical Sciences, 2021)
Galam (Melaleuca cajuputi subsp. Cumingiana (Turcz.) Barlow) is a peat swamp forest plant. This plant is used to treat respiratory diseases, colitis, sore throat, itchy skin, diarrhea, and dizziness. This study aimed to analyze the antibacterial and antifungal activity of the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow flowers and fruit against Escherichia coli and Candida albicans bacteria. This research is a pretest-posttest research with control group design and consists of 3 stages of research. The first stage is the phytochemical screening test, the second stage determines the minimum inhibitory concentration (MIC) and the third determines the minimum bactericidal concentration (MBC). The results showed that the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow flowers and fruit contained terpenoids, flavonoids, phenols, saponins, quinones, steroids, tannins, while alkaloid compounds only found in the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow fruit. The MIC and MBC values ​​of M. cajuputi subsp. Cumingiana (Turcz.) Barlow flower methanol extract against E. coli were 1.67 and 2.083 mg/mL, respectively, while the MIC and MBC values ​​of the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow flower against C. albicans were 3.125 and 25 mg/mL. The MIC and MBC values ​​of the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow fruit against E. coli have same value were 3.334 mg/mL, while the MIC and MBC values ​​of the methanol extract of M. cajuputi subsp. Cumingiana (Turcz.) Barlow fruit against C. albicans were 3.125 and 12.5 mg/mL, respectively. Keywords: Galam antibacterial, antifungal, Escherichia coli, Candida albicans